Renewable Energy Consumption During Covid-19 Pandemic - Pena-Sanchez, Rolando (Archives of Business Research, 2022)
Currently, the pandemic derived from the outbreak of the Covid-19 virus represents one of the most complicated situations for the world economy because it is a health emergency, which has created remarkable affectations in all types of industries, such as the electrical industry. A brief information about the distribution, commercialization, and diversity in power generation sources is included. This report analyzes the annual average change in percent renewable energy consumption from 2019 to 2020 for the representative group of selected countries: China, France, Germany, Italy, Japan, Portugal, Spain, United Arab Emirates, United Kingdom, and United State; where the parametric (paired t-Test), and the non-parametric technique (related-samples Wilcoxon signed rank test) produced the same result: the average annual change in the percentage consumption of renewable energy from 2019 to 2020 has been significant (p-value< 0.01) for the group of selected countries. We conclude this report by proposing the implementation of a new paradigm: The transformation of an energy dependent on oil into one dependent on renewable sources, such as solar radiation and wind mainly.